Health Risk and Safety Perception among Workers in Automotive Repair Shops, Muang District, Nakhon Ratchasima Province - Phetliap, Witchaya; Photipim, Mali (Journal of Vongchavalitkul university, 2020)
Objective: This descriptive research aimed to examine health risk and safety perception among workers in automotive repair shops at Muang District, Nakhon Ratchasima Province. Method: Samples were 114 workers of 8 automotive repair shops. The samples were recruited by using the simple random sampling method. A questionnaire was used for data collection. The statistic utilized for data analysis was descriptive statistic. Results: The results showed that all the subjects were males comprising maintenance technicians (56.1 %) and spray painting workers (43.9 %) with an average age of 33.96 years. Occupational health and safety problems in automotive repair shops consisted of ergonomic hazard, chemical hazard and physical hazard (heat, noise). The most frequent safety behavior of the worker was the appropriate selection of equipment and tool for work (79.8 %). Health risk perception of most of the workers were at medium level (53.5 %). Therefore, related sectors should realize the importance of occupational health and safety problems, promote surveillance plan and safety behavior to increase quality of work life among workers in automotive repair shops.